Determination of energy usage and potential environment impact (pei) of a vapor compression distillation system for production of water for injection (wfi) in pharmaceutical industries - Siti Nabihah, Abdul Latif (2014)
This paper presents the potential environment impact (PET) and energy usage studies of Water For Injection (WFI) manufacturing using vapor compression distillation (VCD) system. The amount of PET were analysed in waste reduction (WAR) algorithm using the amount of energy usage adapted from simulation. The equations used were developed in Excel spreadsheet. There are eight impact categories were calculated to determine the effect from chemical process to the environment. Result from Excel calculation shows that Human Toxicity Potential by inhalation/dermal exposure (HTPE) has the highest value among others impact. The energy usages of VCD system were calculated by simulating the VCD process flow diagram using SuperPro Designer (SPD). The modelling result evaluate that the total energy consumption of WFI from VCD system is 53.07kWh. Since VCD system use electricity as their power supply, therefore some hazardous gases are emitted to atmosphere such as CO2, SO2 and NOx. CO2 has highest amount of emitted from the process with value 112.19. Result from this research may be useful to prevent the excess of CO 2 to our environment.